2006
DOI: 10.1016/s1607-551x(09)70311-0
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Perceived Quality of Life for Adolescents with Physical Disabilities — A Preliminary Study

Abstract: The purpose of this study was to explore the effect of physical disabilities (PD) on the quality of life (QoL) of adolescents aged from 10 to 18 years. Sixty-three adolescents with PD (aged 14.9 +/- 2.4 years) from primary (5th grade or above) to high schools in Kaohsiung City volunteered to participate in this research; 282 children without disability (aged 13.8 +/- 2.3 years) attending schools in the same geographical region were recruited as controls. The Student Version of the Comprehensive Quality of Life… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 14 publications
1
6
2
4
Order By: Relevance
“…This is in agreement with previous studies comparing children with disabilities and typical children (Edwards et al, 2003;Gkoltsiou et al, 2008;Ikeda et al, 2014;Watson & Keith, 2002;Zwicker et al, 2013). In contrast, our results, do not confirm previous studies, which concluded that, despite any differences in the physical functioning domain, children with disabilities display similar or even better HRQOL scores compared with typical children (Albrecht & Devlieger, 1999;Jelsma & Ramma, 2010;Ju et al, 2006;King et al, 1993;Wendelborg & Tøssebro, 2011). Of the above, two studies have been performed in school settings.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…This is in agreement with previous studies comparing children with disabilities and typical children (Edwards et al, 2003;Gkoltsiou et al, 2008;Ikeda et al, 2014;Watson & Keith, 2002;Zwicker et al, 2013). In contrast, our results, do not confirm previous studies, which concluded that, despite any differences in the physical functioning domain, children with disabilities display similar or even better HRQOL scores compared with typical children (Albrecht & Devlieger, 1999;Jelsma & Ramma, 2010;Ju et al, 2006;King et al, 1993;Wendelborg & Tøssebro, 2011). Of the above, two studies have been performed in school settings.…”
Section: Discussionsupporting
confidence: 81%
“…Many factors may account for these differences between studies. First, some studies examined children with various physical disabilities (Ju et al, 2006;Watson & Keith, 2002), intellectual disabilities (Ikeda et al, 2014;Zwicker et al, 2013) or both (present study; Edwards et al, 2003) while one study examined students with chronic illnesses without providing specific information regarding the type or the severity of the illness (Gkoltsiou et al, 2008). Second, the use of the parent-proxy version of the questionnaire might have resulted in lower HRQOL scores than those reported by the children themselves (Achenbach, McConaughy, & Howell, 1987;Jelsma & Ramma, 2010).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Indeed, in a previous study, no correlation was found between objective and subjective QoL in individuals with physical disabilities, while weak to moderate correlations were found between the variables among the controls [26]. However, contrary to the findings of Ju et al [36] and Lui et al [37], polio survivors in this study did not score significantly higher than the controls in subjective QoL. Chow et al [26] had similarly reported no significant difference between the subjective QoL scores of adolescents with physical disabilities and controls.…”
Section: Discussioncontrasting
confidence: 56%